The influence of deviant behavior on individual performance : Case of Kupang district court class 1a - Fina, Jefri S.; Batilmurik, Ridolof W.; Kabu, Enos; Nafi, Sulche (CV. Jala Berkat Abadi, 2024)
This study aims to determine the effect of deviant behavior on individual performance and to determine the effect of deviant behavior on individual performance. This study used a quantitative method with a population of all employees of the Kupang District Court Class 1A. The sampling method uses a non-probability sample method with 40 samples which are all Kupang District Court Class 1A. There are three measuring instruments used in this study, namely a deviant behavior scale of 0.921, an individual performance scale with a reliability of 0.811, and a self-esteem scale with a reliability of 0.840. Based on the test results, it was obtained that the t value of the emotional exhaustion variable was 5.552 with a significant value of 0.000 <0.05. This shows that there is a positive influence from the deviant behavior variable on the employee's deviant behavior. The value of R2 is 0.445 or 44.5%. This means that the contribution of deviant behavior and self-esteem variables to the performance of individual employees is 44.5%. Based on the test results, it was obtained that the t value of the interaction of deviant behavior variables with self-esteem was -3.57 with a significant value of 0.042 <0.05. This shows that the self-esteem variable acts as a moderating variable between deviant behavior variables and individual performance where the moderation formed is complete moderation.